2022
DOI: 10.3390/cancers14143508
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Models and Multiparametric Magnetic Resonance Imaging for the Prediction of Pathologic Response to Neoadjuvant Chemotherapy in Breast Cancer

Abstract: Background: Most breast cancer (BC) patients fail to achieve pathological complete response (pCR) after neoadjuvant chemotherapy (NAC). The aim of this study was to evaluate whether imaging features (perfusion/diffusion imaging biomarkers + radiomic features) extracted from pre-treatment multiparametric (mp)MRIs were able to predict, alone or in combination with clinical data, pCR to NAC. Methods: Patients with stage II-III BC receiving NAC and undergoing breast mpMRI were retrospectively evaluated. Imaging fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…A high recurrence risk score of gene expression panels such as the 21-gene assay on diagnostic biopsy has been shown to predict pCR 47,48 , as well as the assessment of circulating tumor DNA and particularly its early dynamic changes during over the course of NCT 49 . Furthermore, in the BC NCT setting, ML and deep learning models have been explored to predict the pathological response based on pre-NCT histopathological and radiological images [50][51][52] . Thus, the model we speci cally developed for HoR-positive/HER2-negative subtype could be integrated with digital pathology images and radiology features.…”
Section: Discussionmentioning
confidence: 99%
“…A high recurrence risk score of gene expression panels such as the 21-gene assay on diagnostic biopsy has been shown to predict pCR 47,48 , as well as the assessment of circulating tumor DNA and particularly its early dynamic changes during over the course of NCT 49 . Furthermore, in the BC NCT setting, ML and deep learning models have been explored to predict the pathological response based on pre-NCT histopathological and radiological images [50][51][52] . Thus, the model we speci cally developed for HoR-positive/HER2-negative subtype could be integrated with digital pathology images and radiology features.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Kun Chen et al [9] established four PET/CT-based radiomics models that effectively predict pCR in breast cancer patients undergoing NAC, and the AUC of these models ranged from 0.70 to 0.77. Radiomics of multiparametric MRI images can also be employed for predicting the efficacy before NAC [27][28][29][30] . Zhenyu Liu et al [6] developed a radiomics model based on multiparametric MRI images before NAC, with an AUC of 0.79.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated that integrating radiomics features and imaging features extracted from DWI-MRI and DCE-MRI, such as gray-level size-zone matrix, GLCM, and gray-level run length matrix, along with clinical data such as molecular subtype and clinical tumor stage, significantly enhanced performance compared to using clinical or imaging features alone, achieving an accuracy of 91.5%. Collectively, the literature studies presented [233,235,236,[238][239][240] underscore the potential for improving the pre-treatment prediction of tumor response to NAC through the application of AI/ML techniques.…”
Section: The Role Of Ai In the Assessment Of Treatment Responsementioning
confidence: 97%
“…The combination of radiomics features with molecular subtypes notably improved prediction performance, elevating the AUC from 0.72 to 0.80. Vicent et al [240] harnessed six machine learning algorithms (KNN, DT, RF, AdaBoost, GBoost, GNB, LDA, LR, and MLP) to predict tumor response to NAC, classifying it into two categories: pCR and no-pCR. They assessed their algorithms using data from 58 patients collected at Castellón provincial hospital, Spain.…”
Section: The Role Of Ai In the Assessment Of Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation